Segawa syndrome caused by TH gene mutation and its mechanism - Wang, Yilin; Wang, Chunmei; Liu, Meiyan; Xu, Wuhen; Wang, Simei; Yuan, Fang; Luo, Xiaona; Xu, Quanmei; Yin, Rongrong; Wang, Anqi; Guo, Miao; Lin, Longlong; et al. (Frontiers in Genetics, 2022)
Dopa-responsive dystonia (DRD), also known as Segawa syndrome, is a rare neurotransmitter disease. The decrease in dopamine caused by tyrosine hydroxylase (TH) gene mutation may lead to motor retardation, dystonia, tremor and severe encephalopathy in children. Although the disease caused by recessive genetic mutation of the tyrosine hydroxylase (TH) gene is rare, we found that the clinical manifestations of 7 children with TH gene mutations are similar to dopa-responsive dystonia. To explore the clinical manifestations and possible pathogenesis of the disease, we analyzed the clinical data of 7 patients and detected the whole exome gene. Next-generation sequencing showed that the TH gene mutation in 3 children was a reported homozygous mutation (c.698G>A). At the same time, four new mutations of the TH gene were found in other children: c.1004C>T(p.Ala335Val), c.645-2A>G, c.316_317insCGT, and c.832G>A(p.Ala278Thr). We collected venous blood from four patients with Segawa syndrome and their parents for real-time qPCR (RT-qPCR) analysis of TH gene expression. We predicted the structure and function of proteins on the missense mutation iterative thread assembly refinement (I-TASSER) server and studied the conservation of protein mutation sites. Combined with molecular biology experiments and related literature analysis, the qPCR results of two patients showed that the expression of the TH gene was lower than that in 10 normal controls, and the expression of the TH gene of one mother was lower than the average level. It is speculated that mutation of the TH gene may lead to related clinical manifestations by affecting the production of dopamine and catecholamine downstream, which enriches the gene pool of Segawa syndrome. At the same time, the application of levodopa is helpful to the study, diagnosis and treatment of Segawa syndrome.